How professional development can be supported for health and care research methodologists: results of the PROfesSionnal develoPmEnt for Research methodologists (PROSPER) e-Delphi and consensus study - Paula R Williamson; Eleanor J Mitchell; Mais Iflaifel (BMJ Open)
Objective Research methodologists play a pivotal role in health and care research, yet they face many challenges relating to their professional development. The PROfesSional develoPmEnt for Research methodologists study was designed to understand and prioritise the professional development and capacity-building needs of research methodologists in the UK.Design, setting and participants Three-round electronic Delphi (e-Delphi) survey, with input from stakeholders in the development of the candidate list of professional development aspects followed by a national consensus meeting of health and care research methodologists in the UK.Main outcome measures Rated importance of each professional development aspects on a 9-point scale.Results 207 participants gave their consent to participate in the e-Delphi survey. 189 (91%) completed round 1 and 76% completed all three rounds. In round 1, 35 professional development aspects were rated by priority, with 21 additional aspects suggested by participants and included in subsequent rounds. Rounds 2 and 3 involved rating 56 aspects: 22 achieved ‘consensus in’, 20 were ‘consensus out’ and 14 had ‘no consensus’. The top ‘consensus in’ aspects were supportive line managers, clear career pathways and promotion criteria and time for training. A consensus meeting with 18 participants rerated the 14 ‘no consensus’ aspects, adding three more to the final list. The final list includes 25 priority areas for research methodologists’ professional development.Conclusions This study has established the priorities from a professional development perspective for research methodologists. These priorities particularly focus on the importance of support from others, training and development, the value and recognition of the role, employer/contractual agreements and methodological research funding. The list of priorities could help individuals, managers, employers and research funders to improve professional development opportunities and could form the start of the development of a ‘methodologists’ charter’.